Grain yield and quality responses to nitrogen application rate and timing in dry direct broadcast seeded rice under different weather conditions - Tanaka, Ryo; Nakano, Hiroshi (Agrosystems, geosciences & environment, 2024)
In rice (Oryza sativa L.) production, dry direct seeding is one of the most essential technologies to reduce labor input and to increase net income. Field experiments were conducted in southwestern Japan in 2019 and 2020 to determine the effects of nitrogen (N) application rate and timing on grain yield, lodging, grain appearance, and protein content in dry direct broadcast seeded rice under different weather conditions. In 2019, plants had larger source ability using the normal solar radiation at the tillering stage, regardless of N application timings. Plants with applied N at the reproductive stage produced the highest grain yield and the highest percentage of undamaged grains under high air temperature condition during the early ripening stage. In 2020, plants did not have larger source ability due to the lower solar radiation at the tillering stage. Plants with applied N at the reproductive stage produced the highest grain yield but produced the highest percentage of green immature grains. These results mean that solar radiation at the tillering stage may be important for increasing grain yield and quality in dry direct broadcast seeded rice. Therefore, since plants grown under normal solar radiation condition at the tillering stage may have large source ability, more N application at the reproductive stage may be recommended to increase grain yield. In contrast, since plants grown under low solar radiation condition at the tillering stage may have small source ability, less N application at the reproductive stage may be recommended to decrease the occurrence of green immature grains. Core Ideas Grain yield increased by nitrogen (N) application at reproductive. Undamaged grains increased by N application at reproductive under high temperature at ripening. Immature green grains occurred by N application at reproductive under low solar radiation at tillering. Solar radiation at tillering was higher in 2019 than 2020, and grain yield was higher in 2019. Solar radiation at tillering may be important for increasing grain yield and quality in broadcast rice.